Estimation of Transfer of Pollutants from Discharge of Thermal Power Plant (Journal of Nuclear Technology in Applied Science, 2022)
The once -through cooling system of the Suez thermal power plant was chosen to simulate its marine environment impact as a cooling system that may be used in the suggested Egyptian nuclear power plants (ENPPs). To achieve this study, the activity concentrations of their natural radionuclides (238U, 226Ra, 232Th, and 40K) in the collected water samples from the discharge of the Suez cooling system and Suez bay water were measured using a gamma-ray spectrometer. In addition, the physical and chemical properties of the samples were measured. The results of the average activity concentration of natural radionuclides 238U, 226Ra, 232Th, and 40K were 0.053, 0.04, 0.057, and 13.2 Bq/L which were within the permissible limits. The measured activity concentrations of natural radionuclides were used as inputs data in the computer model which uses the mathematical equations to indicate the activity concentration along the Suez coastal waters. It is found that with increasing the distance from the discharge point reached the lowest values of radionuclides concentration 238U, 226Ra, 232Th (0.00351, 0.0, and 0.0 Bq/m3) respectively at the distance 3,500 m from the point of discharge.
Keywords: Natural radionuclides; Pollutants transfer; Suez bay; Thermal power plant; Mathematical model